Amino acid sequence determinants in self‐assembly of insulin chiral amyloid superstructures: Role of C‐terminus of B‐chain in association of fibrils. Issue 6 (14th February 2013) - Babenko, Viktoria; Dzwolak, Wojciech
Abstract : HEWL and HEWLbind by atomic force microscopy (View interaction) Abstract : ► We compare agitation‐assisted aggregation of several proteins. ► Only dimerizing insulins can convert into amyloid chiral superstructures. ► The C‐terminal fragment of the B‐chain binds together individual fibrils.